A single-cell transcriptomic landscape of primate arterial aging - Weiqi Zhang (Nature Portfolio, 2020)
Arterial degeneration, closely associated with cardiovascular diseases, is driven by aging-related vascular cell-specific transcriptomics changes. This study provides a single-cell transcriptomic atlas for senile aortic and coronary arteries and underscores FOXO3A-based the transcriptional network in vasoprotection during aging.